Propriedades mecânicas de argamassas geopoliméricas com a incorporação de pó de vidro e fibra metálica - Vasconcelos, Arthur de Sousa Lima (2025)
The growing need for alternatives to Portland cement is driving the development of sustainable composites. This study evaluated geopolymer mortars based on metakaolin, incorporating glass powder waste, added alumina and reinforced with straight metal fibers, with the aim of investigating the technical feasibility and use of solid waste. Formulations were developed with a partial substitution of 20% of the metakaolin with glass powder and added alumina, and metal fiber contents of 1.0%, 1.5% and 2.0% by volume. The experimental program included tests of consistency index in the fresh state and in the hardened state, axial compressive strength, flexural tensile strength, diametrical compressive strength, dynamic modulus of elasticity, mass density and double punching tensile strength. Microstructural characterizations were carried out using XRD, FTIR and SEM. The results showed that the addition of 2.0% metal fibers promoted a significant increase in flexural tensile strength of 176.69% (15.43 MPa) and axial compressive strength of 46.82% (66.21 MPa). However, the formulation with 1.5% fibers exhibited the best overall performance in terms of mechanical properties, as well as providing increased toughness and improved post-cracking behavior, reducing the initial fragility of the mortars, without compromising the consistency index in the fresh state in relation to the reference. Microstructural characterization showed the consolidation of hydrated sodium aluminosilicate (N-A-S-H) gels with a well-defined structure in the reference composition. The partial incorporation of glass powder and alumina resulted in an increase in the amorphous phase, as shown by Rietveld analysis, indicating changes in the structure of the geopolymer matrix, which was reflected in a reduction in mechanical properties. Nevertheless, the formulations containing glass powder showed adequate performance for structural applications, corroborating the technical viability of using industrial by-products in geopolymer systems as a sustainable alternative for the construction sector.